2009
DOI: 10.1161/hypertensionaha.108.124149
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Increases Blood Pressure, Cerebral Vascular Remodeling, and Severity of Stroke in the Zucker Rat

Abstract: Obesity is a risk factor for stroke, but the mechanisms by which obesity increases stroke risk are unknown. Because microvascular architecture contributes to the outcome of stroke, we hypothesized that middle cerebral arteries (MCA) from obese Zucker rats (OZR) undergo inward remodeling and develop increased myogenic tone compared to lean Zucker rats (LZR). We further hypothesized that OZR have an increased infarct following cerebral ischemia and that changes in vascular structure and function correlate with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(124 citation statements)
references
References 28 publications
9
111
2
2
Order By: Relevance
“…Baseline MAP of the OZR was significantly higher than the LZR under urethane anesthesia (Table 1), as previously reported for conscious adult Zucker rats (5,29). Rectified SNA voltage was also significantly higher in the OZR compared with the LZR (Table 1), in agreement with previous observations of elevated renal and splanchnic SNA in the OZR (16,27).…”
Section: Resultssupporting
confidence: 90%
“…Baseline MAP of the OZR was significantly higher than the LZR under urethane anesthesia (Table 1), as previously reported for conscious adult Zucker rats (5,29). Rectified SNA voltage was also significantly higher in the OZR compared with the LZR (Table 1), in agreement with previous observations of elevated renal and splanchnic SNA in the OZR (16,27).…”
Section: Resultssupporting
confidence: 90%
“…Accordingly, in the present study, structural abnormalities were associated with severe endothelial dysfunction in PAs, whereas structure was preserved in CAs, which displayed a moderate endothelial dysfunction in the same OZRs. Interestingly, PA vascular reactivity and structure were impaired before the onset of hypertension and in contrast to that recently reported for cerebral arteries in this animal model, where structural remodeling, enhanced myogenic tone, and increased stroke risk and injury correlate with the development of hypertension (37). Our findings in PAs of OZRs therefore reinforce the view of ED as an early sign of subclinical vascular disease (46).…”
Section: Discussionsupporting
confidence: 78%
“…However, our own experience suggests that despite marginally extended surgery times, subcutaneous adiposity does not unduly affect success rates. This is also borne out by the recent studies that have emerged combining experimental obesity and stroke (119)(120)(121)(122). All such studies have found that the severity of brain damage is markedly increased in obese rodents compared to corresponding wild-types (see below).…”
Section: Zucker (Fa/fa) Ratsmentioning
confidence: 88%
“…It is only in the last 2 years that studies investigating the impact of obesity on experimental stroke in rodents have emerged (119)(120)(121)(122). All studies have found significantly increased ischemic brain damage in the obese group (see Table).…”
Section: Zucker (Fa/fa) Ratsmentioning
confidence: 99%